Kitar voltametri pengelektroenapan timah dan timah sulfida di atas titanium dalam larutan akueous - Zainal, Zulkarnain; Hussein, Mohd Zobir; Abdul Rashid, Khanisah (Universiti Pertanian Malaysia Press, 1995)
Cyclic voltammetry showed that Sn can be deposited on Ti electrode from aqueous solution containing SnCl2 at overpotential of at least 0.06 V. SnS can also be electrodeposited from the mixture of aqueous solution of SnCl2 and thiosulphate at potential greater than -0.5V vs SCE. The existence of small stripping peak marked Sn element content in the deposit. The stoichiometry of the deposit may be approached by controlling the deposition potential and solution composition.